PROSEDUR PENGUJIAN SUBSTANTIF ATAS SALDO KAS DAN SETARA KAS PT XXX OLEH KANTOR AKUNTAN PUBLIK KANAKA PURADIREDJA, SUHARTONO (NEXIA KPS) - Annisa Rizkyanah Hibatullah Soekamto, (2023)
This Final Project Report discusses the Procedure for Substantive Testing by Cash and Cash Equivalent Balances of PT XXX by KAP Kanaka Puradiredja, Suhartono (NEXIA KPS). Substantive testing means a method of testing and checking the accuracy of the balances contained in the financial statements. The substantive testing procedures include making materiality, controlling confirmation of balances in the relevant bank, vouching, making working papers. A detailed examination of cash and bank accounts is required to recognize the fairness and fairness of the disclosure of financial situation presentations.